TIAM2S Operates Multifaced Talents to Alleviate Radiosensitivity, Restrict Apoptosis, Provoke Cell Propagation, and Escalate Cell Migration for Aggravating Radioresistance-Intensified Cervical Cancer Progression - Pei-Chin Chuang; Wen-Hong Su; Ching-Hua Hsieh; Eng-Yen Huang (Cells)
Radioresistance remains a major obstacle in cervical cancer treatment, frequently engendering tumor relapse and metastasis. However, the details of its mechanism of action remain largely enigmatic. This study delineates the prospective impacts of short-form human T-cell lymphoma invasion and metastasis 2 (TIAM2S) involving the radiation resistance of cervical cancer. In this study, we established three pairs of radioresistant (RR) cervical cancer cells (HeLa, C33A and CaSki) and their parental wild-type (WT) cells. We revealed a consistent augmentation of TIAM2S, but not long-form human T-cell lymphoma invasion and metastasis 2 (TIAM2L) were displayed in RR cells that underwent a 6 Gy radiation administration. Remarkably, RR cells exhibited decreased radiosensitivity and abridged apoptosis, as estimated through a clonogenic survival curve assay and Annexin V/Propidium Iodide apoptosis assay, respectively. TIAM2S suppression increased radiosensitivity and enhanced cell apoptosis in RR cells, whereas its forced introduction modestly abolished radiosensitivity and diminished WT cell apoptosis. Furthermore, TIAM2S overexpression notably aggravated RR cell migration, whereas its blockage reduced WT cell mobilities, as confirmed by an in vitro time-lapse recording assay. Notably, augmented lung localization was revealed after a tail-vein injection of CaSki-RR cells using the in vivo short-term lung locomotion BALB/c nude mouse model. TIAM2S impediment notably reduced radioresistance-increased lung locomotion. This study provides evidence that TIAM2S may operate as an innovative signature in cervical cancer that is resistant to radiotherapy. It displays multi-faceted roles including radioprotection, restricting apoptosis, promoting cell proliferation, and escalating cell migration/metastasis. Targeting TIAM2S, together with conventional radiotherapy, may be an innovative strategy for intensifying radiosensitivity and protecting against subsequent uncontrolled tumor growth and metastasis in cervical cancer treatment.